REDUCTION OF CELL PROLIFERATIVE ACTIVITIES OF GASTRIC STUMP ADENOMATOUS HYPERPLASIAS AFTER BILE REFLUX DIVERSION IN RATS - Imai, T.; Kobayasi, Shoiti [UNESP]; Rodrigues, MAM; Decamargo, JLV; Ogawa, K.; Iwata, H.; Tatematsu, M. (Oxford University Press, 1993)
Previously we reported the majority of lesions induced hy bile reflux, in the absence of chemical carcinogens, in the rat remnant stomach to consist primarily of gastric type and secondarily of intestinal type cells, and that they are reversible after diversion of bile reflux. The present study was designed to evaluate changes in proliferative activities in cells of each type under these conditions. The frequency of adenomatous hyperplasia (AH) induced in the gastric stump mucosa by duodenal content reflux after Billroth II partial gastrectomy (BII) increased until the 54th week of the experiment. Roux-en-Y (RY) surgical procedure which prevents duodenal reflux performed at the 24th or 36th week after BII led to a decrease in AH. Cell content of the lesions was analyzed using routine H&E staining, immunohistochemical staining for pepsinogen isoenzyme 1 and histochemical procedures for mucins (paradoxical concanavalin A, galactose oxidase Schiff and sialidase galactose oxidase Schiff reactions) and proliferation in each compartment evaluated by an immunohistochemical method using bromodeoxyuridine (BrdU) and a monoclonal antibody against BrdU. At the 54th week the number of BrdU-labeled cells per normal pyloric column was significantly (P < 0.05) increased to 10.63/pit after the BII operation, while it diminished to 5.23/pit after RY diversion, this being the same level as with the RY procedure alone. AH maintained a high rate of BrdU incorporation at 12.7% after BII operation, which was also significantly reduced (P < 0.01) to 7.0% by the RY surgery. The intestinal type cell showed highest (22.2%), the surface mucous type cell showed the next (16.5%) and the pyloric gland type cell showed lowest (5.2%) BrdU labeling indices after BII operation. All the cell types in AH showed similar proportional decreases in BrdU incorporation after RY diversion. Thus surgical intervention reverses the cell proliferation caused by bile reflux in the gastric stump.